The deterioration of starch physiochemical and minerals in high-quality indica rice under low-temperature stress during grain filling - Yang, Juan; Zhang, Xinzheng; Wang, De; Wu, Jinshui; Xu, Hang; Xiao, Yang; Xie, Hongjun; Shi, Wanju (Frontiers in Plant Science, 2024)
Low temperatures during the grain-filling phase have a detrimental effect on both the yield and quality of rice grains. However, the specific repercussions of low temperatures during this critical growth stage on grain quality and mineral nutrient composition in high-quality hybrid indica rice varieties have remained largely unexplored. The present study address this knowledge gap by subjecting eight high-quality indica rice varieties to two distinct temperature regimes: low temperature (19℃/15℃, day/night) and control temperature (28℃/22℃) during their grain-filling phase, and a comprehensive analysis of various quality traits, with a particular focus on mineral nutrients and their interrelationships were explored. Exposure of rice plants to low temperatures during early grain filling significantly impacts the physicochemical and nutritional properties. Specifically, low temperature increases the chalkiness rate and chalkiness degree, while decreasing starch and amylopectin content, with varying effects on amylose, protein, and gelatinization temperature among rice varieties. Furthermore, crucial parameters like gelatinization enthalpy (∆H), gelatinization temperature range (R), and peak height index (PHI) all significantly declined in response to low temperature. These detrimental effects extend to rice flour pasting properties, resulting in reduced breakdown, peak, trough, and final viscosities, along with increased setback. Notably, low temperature also had a significant impact on the mineral nutrient contents of brown rice, although the extent of this impact varied among different elements and rice varieties. A positive correlation is observed between brown rice mineral nutrient content and factors such as chalkiness, gelatinization temperature, peak viscosity, and breakdown, while a negative correlation is established with amylose content and setback. Moreover, positive correlations emerge among the mineral nutrient contents themselves, and these relationships are further accentuated in the context of low-temperature conditions. Therefore, enhancing mineral nutrient content and increasing rice plant resistance to chilling stress should be the focus of breeding efforts to improve rice quality.